Communication Governance Based Community Development for Sustainable Coastal and Marine Resource Utilization in Bintan Regency - Yudithia Yudithia; Naureen Savaira Sherazade Darmawan; Mahadiansar Mahadiansar; Ilham Sentosa (Yayasan Darussalam Bengkulu, 2026)
This study examines community development based on communication governance in supporting sustainable coastal and marine resource utilization in Bintan Regency, Indonesia. Bintan’s coastal and marine areas possess significant ecological and socio-economic value, particularly through coral reef, seagrass, and mangrove ecosystems that sustain fisheries, tourism, and local livelihoods. However, these resources face increasing pressure from mass tourism, plastic pollution, destructive fishing practices, weak environmental compliance, and climate change impacts. The purpose of this study is to analyze how communication governance, institutional coordination, and community participation contribute to strengthening sustainable marine resource management. Using a qualitative descriptive-analytical approach, this study reviews literature, policy documents, and previous research through the Socio-Ecological Systems framework, supported by SWOT analysis to identify internal and external factors influencing governance performance. The findings show that Bintan Regency has a relatively strong regulatory and institutional foundation, including the establishment of Marine Protected Areas and the implementation of national policy instruments such as Presidential Regulation No. 120 of 2020. Nevertheless, governance effectiveness remains constrained by limited institutional capacity, inadequate funding, fragmented stakeholder communication, and weak law enforcement. The study argues that sustainable coastal and marine resource utilization requires adaptive, participatory, and communication-oriented governance that connects local government, coastal communities, tourism actors, and conservation institutions.